Law: key concepts in philosophy - "Ingram, David" (London, 2006)
Key Concepts in Philosophy is a series of concise, accessible and engaging introductions to the core ideas and subjects encountered in the study of philosophy. Specially written to meet the needs of students and those with an interest in, but little prior knowledge of, philosophy, these books open up fascinating, yet sometimes difficult ideas. The series builds to give a solid grounding in philosophy and each book is also ideal as a companion to further study. The philosophy of law - inquiry into the origins, nature and theory of laws and legal principles, and those concepts that structure the practice of law - is of great importance in moral and political philosophy, as well as being a major area of philosophical concern in its own right. Clear, concise and comprehensive, this is the ideal introduction to the philosophy of law for those studying it for the first time. Drawing upon both the analytic Anglo-American and Continental schools of philosophy, Law: Key Concepts in Philosophy summarises the work of key thinkers in the philosophy of law, including Rousseau, Hobbes, Austin, Hegel, Mill, Marx, Dworkin and Rawls. It provides lucid and thorough explication and analysis of central concerns in legal philosophy, covering criminal law, civil law and constitutional law. Finally, the text also addresses key issues in contemporary philosophy of law, including human rights, international law and questions of race and gender.
Keywords: Law